The Emerald handbook of destination recovery in tourism and hospitality - Mohanty, Priyakrushna; Sharma, Anukrati; Kennell, James; Hassan, Azizul (Emerald Publishing Limited, 2022)
The Emerald Handbook of Destination Recovery in Tourism and Hospitality deals with three major objectives: exploration of the various ways to put the tourism industry on the path of recovery following global COVID-19 pandemic; to envisage strategies to make tourism more resilient; and to explore sustainability and its vital importance post-crisis. Core themes examined across the collected chapters include tourism and hospitality start-ups in times of crisis, innovative marketing strategies driving tourism recovery, building trust among tourists in the post COVID-19 period, and re-engineering tourism education.